2011
DOI: 10.1128/iai.05070-11
|View full text |Cite
|
Sign up to set email alerts
|

Glycogen Synthase Kinase 3 Activation Is Important for Anthrax Edema Toxin-Induced Dendritic Cell Maturation and Anthrax Toxin Receptor 2 Expression in Macrophages

Abstract: Anthrax edema toxin (ET) is one of two binary toxins produced by Bacillus anthracis that contributes to the virulence of this pathogen. ET is an adenylate cyclase that generates high levels of cyclic AMP (cAMP), causing alterations in multiple host cell signaling pathways. We previously demonstrated that ET increases cell surface expression of the anthrax toxin receptors (ANTXR) in monocyte-derived cells and promotes dendritic cell (DC) migration toward the lymph node-homing chemokine MIP-3␤. In this work, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 51 publications
(69 reference statements)
0
20
0
Order By: Relevance
“…While there have been several studies examining ET neutralization with commercially available immunoassay-based cAMP detection reagents, none of these assays generated reproducible data with human serum samples in our hands, possibly due to interference from serum or plasma constituents. To measure ET neutralization reproducibly, we employed a cAMP-inducible luciferase reporter cell line (40). This assay resulted in 95.4% (103/108) and 100% (108/108) of repeated experiments having neutralization values within 12% and 26%, respectively, of the first experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While there have been several studies examining ET neutralization with commercially available immunoassay-based cAMP detection reagents, none of these assays generated reproducible data with human serum samples in our hands, possibly due to interference from serum or plasma constituents. To measure ET neutralization reproducibly, we employed a cAMP-inducible luciferase reporter cell line (40). This assay resulted in 95.4% (103/108) and 100% (108/108) of repeated experiments having neutralization values within 12% and 26%, respectively, of the first experiment.…”
Section: Resultsmentioning
confidence: 99%
“…Cyclic AMP production and ET neutralization were assessed using a RAW 264.7 cAMP response element (CRE) luciferase reporter cell line (40). Cells (100,000/well) were cultured in 96-well plates for 18 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…Only Voth et al have reported ET to be directly cytotoxic to both zebrafish embryos and RAW264.7 macrophage-like cells [241]. However, ET inhibits cell cycle progression in the J774.1A and RAW264.7 macrophagelike cell line [197,230]. It is unknown if this delay leads to apoptosis or whether it is unique to macrophages.…”
Section: Immunological Effectsmentioning
confidence: 99%
“…LT has been shown to inhibit chemotaxis in PBMC's; however, addition of purified LT with ET also leads to an increase in chemotaxis compared to untreated DCs [193,196]. Additionally, recombinant ET is capable of activating glycogen synthase kinase (GSK) in DCs, which in turn is able to fully activate CREB-mediated transcriptional changes shown by Kim et al to be involved with chemotaxis [194,197]. It is unknown if GSK is involved with CREB activation in either neutrophils or macrophages.…”
Section: Immunological Effectsmentioning
confidence: 99%
See 1 more Smart Citation